Analisis Determinan Volume Ekspor Batubara Indonesia Ke Tiongkok (Lembaga Pengembangan Kinerja Dosen, 2025)
Coal is one of the strategic mining commodities for Indonesia, both in its role as the main source of domestic energy and as a contributor of foreign exchange from the export sector. Indonesia is known as one of the largest producers and exporters of coal in the world, especially the type of thermal coal used for power generation. China is the world's largest energy consumer, with coal accounting for about half of its total energy needs. As a fast-growing industrialized country, China needs a large supply of coal to support power generation and heavy industries such as steel and cement. This study aims to analyze the simultaneous influence of international prices, the development of iron and steel industry production, and the USD exchange rate on the volume of Indonesian coal exports to China and analyze the influence of international prices, the development of iron and steel industry production, and the partial USD exchange rate on the volume of Indonesian coal exports to China. The data analysis technique used in this study is multiple linear regression. The results of the study found that international prices, the development of iron and steel industry production, and the USD exchange rate had a simultaneous significant effect on Indonesia's foreign exchange reserves, and partially the USD exchange rate had a positive and significant effect on the volume of Indonesia's coal exports to China, while international prices partially had a positive but insignificant effect and the development of iron and steel industry production partially had a negative effect but not statistically significant to the volume of Indonesia's coal exports to China. By maintaining the stability of the rupiah exchange rate against foreign exchange, it will be very helpful in maintaining and increasing the volume of Indonesia's coal exports to China.